1999
DOI: 10.1007/s004210050620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-day “live high, train low” camp on reticulocyte production and haemoglobin mass in elite female road cyclists

Abstract: The aim of this study was to document the effect of "living high, training low" on the red blood cell production of elite female cyclists. Six members of the Australian National Women's road cycling squad slept for 12 nights at a simulated altitude of 2650 m in normobaric hypoxia (HIGH), while 6 team-mates slept at an altitude of 600 m (CONTROL). HIGH and CONTROL subjects trained and raced as a group throughout the 70-day study. Baseline levels of reticulocyte parameters sensitive to changes in erythropoeisis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
4
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 30 publications
4
47
4
1
Order By: Relevance
“…6 7 Results of studies on the effects either of living and training at moderate altitude or of living at moderate altitude and training at low altitude on total haemoglobin mass (red cell volume) and sea level performance are controversial. [8][9][10][11][12][13][14][15][16] In most of the studies with elite athletes, total haemoglobin mass was not significantly increased after living and training at moderate altitude.…”
Section: Discussionmentioning
confidence: 99%
“…6 7 Results of studies on the effects either of living and training at moderate altitude or of living at moderate altitude and training at low altitude on total haemoglobin mass (red cell volume) and sea level performance are controversial. [8][9][10][11][12][13][14][15][16] In most of the studies with elite athletes, total haemoglobin mass was not significantly increased after living and training at moderate altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to recognize that short-term exposure to acute hypoxia may increase hematocrit and hemoglobin concentration by hemoconcentration and may increase reticulocyte counts by release of immature red cell forms from the bone marrow, without a true acceleration of erythropoiesis (Gunga et al, 1996). Some investigators, failing to observe an increase in hemoglobin-myoglobin mass after brief periods of time in normobaric hypoxic environments (8 to 10 h/night for 10 d for 3 weeks) have questioned the erythropoietic effect of moderate altitude exposure altogether (Ashenden et al, 1999a(Ashenden et al, , 1999b(Ashenden et al, , 2000, and it seems certain from these data that, under the 180 LEVINE specific conditions of these experiments, sleeping in a nitrogen-enriched environment may in fact not be erythropoietic. Although short-duration exposures of less than 10 h for less than 3 weeks do not raise red cell mass in the Australian experience (Ashenden et al, 1999a(Ashenden et al, , 1999b(Ashenden et al, , 2000, Finnish investigators have been able to demonstrate increases in red cell mass (using the same technique, carbon monoxide rebreathing, as the Australian investigators using shorter-term exposures) with 16 h of hypoxia/night for 4 weeks (Laitinen et al, 1995;Rusko et al, 1999).…”
Section: Erythropoietic Effect Of High Altitudementioning
confidence: 99%
“…2 Apparently at variance with this concept, several studies have shown unchanged Hb mass and/ or EV after LHTL or living high and training high, [3][4][5][6][7][8][9][10] but critical inspection of their data indicates that either the selected altitude for ''living high'' was probably 11 too low, 6 8-10 and/or the duration was too short. [3][4][5] Rusko et al 12 indicated that the hypoxic stimulus to increase Hb mass and EV should be least 400 hours at 2300-2500 m. Several studies 2 13-15 have shown increased Hb mass or EV after LHTL with this stimulus. However, the athletes in these studies were not reported to be world class.…”
mentioning
confidence: 99%